PELATIHAN MERAKIT KOMPUTER BAGI WARGA DESA SUKOSARI KEC. BANDONGAN KAB. MAGELANG - Muchammad Hifni; Feri Annur Styawan; Daffa Erangga Ardi Putra; Dwiranda Ariel Aliansyah (PPM Sdirjianbang Akademi Militer, 2023)
In this era of advanced technology, the need for computer assembly skills is increasing which is influenced by several factors including increased market demand, flexibility in meeting customer needs, cost savings, promising business benefits and increasing business credibility. Furthermore, lecturers and students of the defense electronics engineering study program of the Military Academy conducted community service activities in Sukosari Village, Bandongan District, Magelang. With computer assembly training, about 60% of the community as trainees were able to receive the material well. This is obtained from the level of enthusiasm and the results of the test before and after the activity. The output of the activity is that the community is able to open business opportunities in the computer field